Deep Understanding of Electron Beam Effects on 2D Layered Semiconducting Devices Under Bias Applications. Issue 9 (6th February 2022) - Lee, Kookjin; Ji, Hyunjin; Kim, Yanghee; Kaczer, Ben; Lee, Hyebin; Ahn, Jae‐Pyoung; Choi, Junhee; Grill, Alexander; Panarella, Luca; Smets, Quentin; Verreck, Devin; Van Beek, Simon; et al.
Abstract: In this study, the radiation effects of electron beam (e‐beam) on field‐effect transistors (FETs) using transition‐metal dichalcogenides (TMD) as a channel are carefully investigated. Electron‐hole pairs (EHPs) in SiO2 generated by e‐beam irradiation induce additional traps, which change the surface potential of the TMD channel, resulting in strong negative shifts of transfer characteristics. These negative shifts, which remind one of n‐doping effects, are highly affected not only by the condition of e‐beam irradiation, but also by the gate bias condition during irradiating. As a result of the e‐beam irradiation effect, band bending and contact resistance are affected, and the degree of formation of oxide traps and interface traps varies depending on the gate bias conditions. In the case of V G > 0 V application during e‐beam irradiation, the negative shifts in the transfer characteristics are fully recovered after ambient exposure. However, the interface traps increase significantly, resulting in variations of low‐frequency (LF) noise and time‐dependent current fluctuations. Abstract : Regardless of the type or the thickness of the channel, holes of electron‐hole pairs generated by electron beam (e‐beam) irradiation are trapped in SiO2, resulting in negative shifts of transfer curves according to different bias applications. Understanding and interpretation of the e‐beam effect are conducted in parallel with DC analysis, time‐dependent current, and low‐frequency noise.